Kenneth Waltz's approach to reading classic political theory and why it matters. Issue 2 (3rd July 2022) - MacKay, Joseph
Abstract: How did Kenneth Waltz read canonical theoretical texts? Waltz understood himself first as a political theorist and remained committed to interpreting political thought throughout his career. This paper briefly delineates Waltz's method for reading political theory. I identify four elements of Waltz's approach: it was purposive, explanatory, textualist, and anti-esoteric. First, he thought texts could best be linked to one another and compared purposively, by aligning the questions they asked. Second, he understood the primary purpose of theoretical texts to be explanatory: normativity was a secondary concern. Third, he was a relatively strict textualist, taking little interest in historical context. Fourth, he took no account of esoteric writing. I then track his intellectual influences, through his graduate training and early academic career. I show this set of methodological tenets was, taken together, largely his own invention. I argue Waltz's reading method shaped his own theoretical work, providing concepts and informing his structural and parsimonious style of theory. I track these effects in his later theory-building project in Theory of International Politics . By extension, I suggest, his approach influenced much of postwar International Relations theory, both in terms of its specific conceptual toolkit and its approach to theory as such.